Innovations in Computer Science and Engineering Proceedings of the Fifth ICICSE 2017 - Saini, H. S.; Sayal, Rishi; Govardhan, A.; Buyya, Rajkumar (Lecture Notes in Networks and Systems, 2019)
The book is a collection of high-quality peer-reviewed research papers presented at the Fifth International Conference on Innovations in Computer Science and Engineering (ICICSE 2017) held at Guru Nanak Institutions, Hyderabad, India during 18-19 August 2017. The book discusses a wide variety of industrial, engineering and scientific applications of the engineering techniques. Researchers from academic and industry present their original work and exchange ideas, information, techniques and applications in the field of Communication, Computing and Data Science and Analytics.